MORPHOMETRICS OF TIRASIANA FROM VENDIAN OF PODILLIA (UKRAINE) - Mienasova, А.; Popova, L.; Dzeverin, І. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Tirasiana Palij, 1976 is a genus of radially symmetric Vendobionts, which were preserved as a positive hyporelief of two superimposed discs. Tirasiana are found in the Vendian deposits of the Podolian Dnister area, the White Sea area and the Urals. For better understanding of the nature and lifestyle of Vendian biota, imprints of the Tirasiana were investigated by statistical methods. Sampling of 29 specimens of Tirasiana was studied. To test the hypothesis about the allometric growth of Tirasiana, two features were studied, the diameters of the outer and inner discs. As a result of the study, it has been established that the relationship between internal and external diameters of the imprints is almost ideally isometric, which means that there is no evidence for relation between Tirasiana and Cnidaria. The distribution patterns of these features were analyzed and the assumption about their normality was tested. Histograms of their distribution and empirical additional cumulative distribution functions were constructed. Based on the assumption of the constant growth of Tirasiana throughout onthogenesis and the proportionality of the linear size and individual age, the cumulative distribution functions may be considered as survival curves in the sampling of specimens of Tirasiana and may be analyzed by standard methods accepted in ecology. If we accept this assumption, then the survival curve of the first type is characteristic of the Tirasiana, which corresponds to the increase of probability of their death with the increase of individual age. The studied taphocenosis was formed as a result of accumulation of terrigenous material, which came from the nearby land that was not stabilized by vegetation. This terrigenous sediment buried benthic sublittoral communities regularly. The heterogeneity of the sampling of specimens can be explained by the presence of "survival stations", well-protected parts of the palaeobasin (overhanging rocks, baybar, etc.). As a result, in such places Tirasiana could attain much larger size.
Keywords: Tirasiana; Vendian biota; metazoa; Podolian Dnister area; isometric and allometric growth; survival curves